Perception of nasal aesthetics: Nose or face - BAYRAMİÇLİ, MEHMET NURİ ÜMİT (My University, 2022)
Background Aesthetic assessment of the nose might not be limited to the nose as an isolated facial unit but might be the result of a broader perception of the whole facial image. The aim of this study was to investigate if the aesthetic evaluation of a nose is made by sole observation of the nose or influenced by the other features of the face. Methods Nose and face photographs of 20 voluntary models were taken from five different angles and merged into a single image of just the noses and whole faces of each model. First the nose and then the face photos were sent to a reviewer group consisting of 100 individuals from different professions to evaluate the nose’s beauty on standard questionnaires with a four-week interval to complicate the recall process. Results Aesthetic evaluation of the isolated nose (Group 1) and the nose with the whole face (Group 2) were compared through Visual Analog Scale (VAS) scores ranging from 1 to 10 (1: the least, 10: the highest). The mean VAS score of the Whole Face Group (5.26 ± 1.28) was significantly higher than the score of the Isolated Nose Group (4.50 ± 1.32) (p 0.001). There was no significant difference between the scores of reviewers considering their gender, profession, or experience of having an aesthetic operation previously. Conclusion Current study revealed that in the evaluation of the beauty of the nose, the holistic perception of the face is as important as the perfection of the angles and proportions within the nose itself.
Keywords: Tıp; Sağlık Bilimleri; Cerrahi Tıp Bilimleri; Medicine; Health Sciences; Surgery Medicine Sciences; CERRAHİ; Klinik Tıp; Klinik Tıp (MED); SURGERY; CLINICAL MEDICINE; Clinical Medicine (MED); Cerrahi; Surgery; Nasal aesthetics; Attractive nose; Facial attractiveness; Beauty perception; Facial features; Visual impression; PATIENT SATISFACTION; RHINOPLASTY; BEAUTY; PROPORTIONS; IMPACT; Nasal aesthetics; Attractive nose; Facial attractiveness; Beauty perception; Facial features; Visual impression